PENGARUH STRATEGIS PEMASARAN DIGITAL DAN MEDIA SOSIAL TERHADAP BRAND AWARENESS DI INDUSTRI - Pebrianti, Resa Pelisa (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
The fashion industry is currently facing a dynamic digital era, where digital marketing strategies and social media are the main keys in increasing brand awareness. This research aims to analyze the influence of digital marketing strategies and social media on brand awareness in the fashion industry. The research method used is quantitative with statistical data analysis techniques using SPSS. Data was collected through an online survey distributed to the fashion industry target market. The research results show that digital marketing strategies and social media have a significant influence on brand awareness in the fashion industry. These findings show the importance of implementing effective digital marketing and social media strategies to increase brand awareness and achieve success in the competitive fashion industry.